Polymicrobial interactions influence the agr copy number in Staphylococcus aureus isolates from diabetic foot ulcers - Matias, C (2019)
Diabetic foot ulcers are a major complication of diabetes and are often colonised by complex bacterial communities, where Staphylococcus aureus is frequently co-present with Pseudomonas aeruginosa. These bacteria interact through quorum sensing, encoded in S. aureus by the accessory gene regulator (agr). Typing and copy number of S. aureus agr were assessed here to give insights on strain variability and possible interspecies influence. As agr is classified in four genetic groups, agr-I, agr-II, agr-III and agr-IV, the agr type of 23 S. aureus diabetic foot ulcers isolates was evaluated by PCR and gene copy number determined by qPCR, including in S. aureus present in polymicrobial infections. agr-I and agr-II were found to be present in 52 and 39% of the isolates, respectively. In two isolates, no agr type was identified, and types III and IV were not detected. Interestingly, agr-II copy number was higher in dual suspensions than in S. aureus single suspension. We conclude that agr type I was the most frequent in clinical centers in Lisbon, and variations in agr-I and agr-II copy numbers were strain specific. Variations in agr copy number in dual suspensions suggests that P. aeruginosa may influence S. aureus agr-II gene regulation, confirming an interaction between these two bacteria. This is a first approach to characterise agr variation in S. aureus from diabetic foot ulcers in vitro.